Imitating Christ's Cross: Lonergan and Girard on How and Why. (29th October 2012) - Miller, Mark T.
Abstract : The article begins with the gospels' admonition to take up one's cross and asks how Christians might understand Christ's work on the cross so that we might better imitate or participate in it. Using tools from recent advances in literary analysis and systematic theology, the article attempts to provide some answer to this question. It considers contemporary feminist and liberation theologians' criticism of the common but problematic interpretation of Christ's cross, what is often called 'substitutionary penal atonement.' It compares this with Anselm's atonement theory of satisfaction and Bernard Lonergan's and René Girard's analysis of the cross as a communication of love that invites others into loving relationship. With these interpretations of Christ's work, it concludes with some thoughts on how Christians might take up their own daily crosses.